Microstructural characterization of biobased carbon foam by means of X-ray microtomography and compared to conventional techniques. Issue 98 (7th October 2016) - Merle, Juliette; Sénéchal, Pascale; Guerton, Fabrice; Moonen, Peter; Trinsoutrot, Pierre; Birot, Marc; Charrier-El Bouhtoury, Fatima
Abstract : The objective of this work is to compare three techniques for characterizing the morphology of porous bio-based carbon foam, namely mercury intrusion porosimetry, scanning electron microscopy and X-ray microtomography. Abstract : The objective of this work is to compare three techniques for characterizing the morphology of porous bio-based carbon foam, namely mercury intrusion porosimetry, scanning electron microscopy and X-ray microtomography. The first two techniques are commonly used in this field, while X-ray microtomography is a more recent characterization technique derived from medical tomography. Our study demonstrates the added value of the latter technique, especially concerning the evaluation of porosity, cell size distributions and cell connectivity. In this study we have shown that the material have a total porosity of around 90% with a cell size of less than 100 microns.